Dynamic expression and essential functions of Hes7 in somite segmentation - Bessho, Yasumasa (Cold Spring Harbor Laboratory Press, 2001)
The basic helix–loop–helix (bHLH) gene Hes7, a putative Notch effector, encodes a transcriptional repressor. Here, we found that Hes7 expression oscillates in 2-h cycles in the presomitic mesoderm (PSM). In Hes7-null mice, somites are not properly segmented and their anterior–posterior polarity is disrupted. As a result, the somite derivatives such as vertebrae and ribs are severely disorganized. Although expression of Notch and its ligands is not affected significantly, the oscillator and Notch modulator lunatic fringe is expressed continuously throughout the mutant PSM. These results indicate that Hes7 controls the cyclic expression of lunatic fringe and is essential for coordinated somite segmentation.